O wychowaniu literackim jako procesie wychowania estetycznego i podstawach tej dyscypliny naukowej = On Literary Education as a Process of Aesthetical Education and on Elements of this Science's Branch - Plch, Jaromir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author refers to former publications, characterizes the up-todate achievements in the theory of literary education and reveals the descriptive only and static formulation of these problems. In the second part of his work the author explicates a dynamic theory of his own: the didactic and aesthetic interactions. In his considerations he refers to the achievements of Marxist philosophy, literatures and aesthetics. The author tries to define the specific charakteristics of the process of education by means of the art of words. The last part of his work contains considerations on methodological elements of literary didactics as a science.
Keywords: wychowanie literackie; wychowanie estestyczne; język czeski